Thermodynamic Properties of Supported and Embedded Metallic Nanocrystals: Gold on/in SiO(2) - Ruffino, F (Springer, 2008)
We report on the calculations of the cohesive energy, melting temperature and vacancy formation energy for Au nanocrystals with different size supported on and embedded in SiO(2). The calculations are performed crossing our previous data on the surface free energy of the supported and embedded nanocrystals with the theoretical surface-area-difference model developed by W. H. Qi for the description of the size-dependent thermodynamics properties of low-dimensional solid-state systems. Such calculations are employed as a function of the nanocrystals size and surface energy. For nanocrystals supported on SiO(2), as results of the calculations, we obtain, for a fixed nanocrystal size, an almost constant cohesive energy, melting temperature and vacancy formation energy as a function of their surface energy; instead, for those embedded in SiO(2), they decreases when the nanocrystal surface free energy increases. Furthermore, the cohesive energy, melting temperature and vacancy formation energy increase when the nanocrystal size increases: for the nanocrystals on SiO(2), they tend to the values of the bulk Au; for the nanocrystals in SiO(2) in correspondence to sufficiently small values of their surface energy, they are greater than the bulk values. In the case of the melting temperature, this phenomenon corresponds to the experimentally well-known superheating process.